Checklist of Indian Harpalinae Bonelli, 1810 (Coleoptera: Carabidae) - Nijisha, K.; Sabu, K. Thomas (Zootaxa, 2023)
An updated checklist of 169 species of subfamily Harpalinae known from the Indian mainland, along with details of the revisions by modern workers, literatures and distribution patterns is provided. Of them, 39 species are endemic to the Indian mainland, whereas 11 species to the Western Ghats Hotspot of Biodiversity, one to the Indo-Burma Hotspot of Biodiversity and eight to the Himalaya Hotspot of Biodiversity. Four genera, Allosiopelus Ito, 1995, Indocarterus Kataev & Wrase, 2018, Oesyperus Andrewes, 1923 and Panagrius Andrewes, 1933 are endemic to the Indian mainland.